Notranja oksidacija zlitin srebra z žveplom - Horvat Kovačič, Saša (Kovine zlitine tehnologije, 1998)
In silver-sulphur alloys, when exposed in air or pure oxygen at high temperature, the internal oxidation occurs. Because of the low solubility of sulphur in silver two phases are present. The products of internal oxidation of these alloys are gaseous. The kinetics of oxidation at high temperature and activation energy of this process were determined and aslo mechanism of internal oxidation was analised.
Keywords: zlitine; srebro; žveplo; oksidacija; kemijska kinetika